Impact of Job Satisfaction on Turnover Intentions among University Teaching Staff - Sehrawat, Parul; Saluja, Prerna Dawar (Journal of Advanced Research in Humanities and Social Sciences, 2021)
The present study measures the impact of job satisfaction on turnover intentions in the private universities teaching staff of Punjab. A sample of 300 university teaching faculty was studied. Proportionate stratified random sampling technique was used for the selection of respondents. After ensuring the normality of the data, factor analysis was conducted to reduce the data into factors. After that, multiple regressions were applied in order to find out the impact of job satisfaction on turnover intention. The results of the study highlighted that different factors of job satisfaction viz; time management and organizational support, leave policy and job security, organizational culture and job pressure were found to have a significant negative impact on urgency of quitting job and have a negative impact on the intention to leave among the teaching staff. Besides these, the paper also presents the managerial implications, limitations and future research of the study. How to cite this article:  Sehrawat P, Saluja PD. Impact of Job Satisfaction on Turnover Intentions among University Teaching Staff. J Adv Res Humani Social Sci 2020; 7(4): 6-19.